Sufficiency Economy Application: Lessons Learned from Kokmueng Community Bangriang, Kaunniang, Songkhla - บัวใหม่ แทนพันธ์ เสนะพันธุ์; สบายยิ่ง มาลี (Journal of Social Sciences and Humanities Research in Asia, 2018)
The research for lesson learned sticks to qualitative research with the purpose to study the driving process to turn the community into a Sufficiency Economy Community. The lesson learned mainly came from storytelling method from the major informants which are 1) Community’s leader, 2) Representative of those who work in community development and 3) Representative of Production Unit in the related community. The total informants are 9 persons. The in-depth interview and semi-structural interview were applied. The information collection was by focus group discussion and the result would be moved to analytic induction process. Furthermore, the lesson learned from storytelling and focus group discussion would be examined by documentation and literature review, including triangulation in terms of time, place and personnel. The research would be presented as descriptive research. The result found that the driving process to turn the community into a Sufficiency Economy Ban Kokmuang Community consists of the 5 subsequent processes as follows: 1) Motivation and Awareness, 2) Community Empowerment, 3) Co-operation to develop the community on sufficient economic dimension, 4) Create sufficient lifestyle after regaining human capital and 5) Community Lesson. These processes are based on these 3 uccessful factors as follows: 1) Having complete human capital in preparation for driving the community development, 2) Ability to create activities or projects for community development and 3) Community’s readiness. Keywords: community development, community empowerment, philosophy of sufficiency economy, self-sufficient Community.